Political private international law: how European are overriding mandatory provisions and public policy exceptions? - Weller, Marc-Philippe; Schulz, Alix (How European is European private international law?, 2019)
INTRODUCTIONToday, Private International Law is increasingly political. Savigny's neutral, universal and multilateral approach to conflict of laws is being steadily given up. This development from neutrality to political values is due to several factors.First, European core values as set forth in Art. 3 of the Treaty on European Union are promoted in all areas of EU law. Consequently, political values such as promotion of gender equality or the protection of weaker parties are nowadays also implemented in Private Law relationships.Second, the societal and political interests of the European Member States are increasingly enforced through Private Law. For example, embargos against countries which are violating values of Public International Law (e.g. North Korea, Russia or Iran) are now often imposed by means of Private Law: embargos can be classified as so called ‘overriding mandatory provisions’ and therefore render all forbidden contracts concluded with firms from the affected States invalid irrespective of the applicable lex contractus.This chapter aims to take a closer look at the evolution of Private International Law from a neutral to a political subject. Special regard will be had to two of the most political instruments of Private International Law: public policy exceptions (ordre public) and overriding mandatory provisions.Furthermore, this chapter will discuss whether this evolution is a truly European development: is it driven by European politics or promoted by the politics of the different Member States?Before looking at public policy exceptions (section 4) and overriding mandatory provisions (section 5) - both explicit ways to enforce political values (section 3) - implicit ways of enforcing political interests in Private International Law will be examined (section 2).IMPLICIT WAYS TO ENFORCE POLITICAL INTERESTSPOLITICAL INTERESTS VERSUS SAVIGNY's CLASSICAL APPROACHWhen studying modern European Private International Law, it is striking that European conflict of laws provisions appear increasingly political. While States’ regulatory interests did not play a significant role in the national conflict of laws systems in the 20th century, European Private International Law of the 21st century aims to achieve political goals: weaker parties, such as consumers or employees, are not only protected through substantive national law, but also by conflict of laws rules which are ‘politically charged’ in their favour.
Gesehen am 21.10.2021